PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT PRATAMA ABADI INDUSTRY - Siti Rohayati; Julidinsah Julidinsah (PT Naureen Digital Education, 2022)
The purpose of this study was to determine the effect of work motivation and job satisfaction on turnover intention at PT. Pratama Abadi Industry JX. The number of samples used in this study were 80 respondents who were determined using the Slovin formula. The data analysis method used is validity test, reliability test and multiple linear regression. The results of the study indicate that either partially or simultaneously work motivation and job satisfaction have a significant effect on turnover intention at PT. Pratama Abadi Industry JX